2020
DOI: 10.1177/1352458520939008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of brain and spinal cord lesion distribution criteria at disease onset in distinguishing NMOSD from MS and MOG antibody-associated disorder

Abstract: Objective: To validate the recently proposed imaging criteria in distinguishing aquaporin-4 antibody (AQP4-ab)-seropositive neuromyelitis optica spectrum disorder (NMOSD) from multiple sclerosis (MS) and myelin oligodendrocyte glycoprotein antibody-associated disorder (MOG-AD) at disease onset in a Chinese population. Methods: We enrolled 241 patients in this retrospective study, including 143 AQP4-ab-seropositive NMOSD, 73 MS, and 25 MOG-AD. Cacciaguerra’s criteria were described as fulfillment of at least 2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
1
16
0
1
Order By: Relevance
“…This remains a significant dilemma in East Asian populations, where the prevalence of MS is lower and atypical forms of inflammatory CNS disease are the norm. In these cases MR imaging is of considerable potential value in determining the underlying cause [165]. However, continued work to find more precise diagnostic features on MRI is needed.…”
Section: Discussionmentioning
confidence: 99%
“…This remains a significant dilemma in East Asian populations, where the prevalence of MS is lower and atypical forms of inflammatory CNS disease are the norm. In these cases MR imaging is of considerable potential value in determining the underlying cause [165]. However, continued work to find more precise diagnostic features on MRI is needed.…”
Section: Discussionmentioning
confidence: 99%
“… 90 Cacciaguerra’s criteria, originally validated in a European cohort, have since been applied in a Chinese population to study their utility in a non-white population. 91 Using a threshold of at least 3/5 criteria to distinguish NMOSD from MS, accuracy was 92%, sensitivity 91%, and specificity 93%. The criteria, however, failed to differentiate NMOSD from MOGAD.…”
Section: Diagnosismentioning
confidence: 94%
“…However, there has yet to be a clear distinction found. 35,81 Evaluation of advanced MRI metrics in NMOSD and MOGAD could offer more discriminatory power, and elucidate microstructural differences in the CNS between patients with NMOSD and MOGAD. 85 whereas other studies have found some decreases in volumes.…”
Section: Advan Ced Mag Ne Ti C Re Sonan Ce Imag Ing Char Ac Teris Tmentioning
confidence: 99%
“…Due to the difference in cellular targets between AQP4‐IgG and MOG‐IgG, it would be expected that conventional MRI characteristics would differ between the two disease entities. However, there has yet to be a clear distinction found 35,81 …”
Section: Advanced Magnetic Resonance Imaging Characteristicsmentioning
confidence: 99%